Chilean Educational Reform: The balance between Macro and Micro Policy - Dagmar Raczynski; Gonzalo Muñoz (Universidad Autónoma de Madrid, 2018)
The Chilean educational system is critical time. From the student mobilization of half-full of 2006 the Chilean Educative Reformation has been put in cuestión. Two questions are emerging: (1) Why, in spite of all the efforts and investments made from 1990 to date, the educative system has not managed to constitute itself in a source of development and equitable distribution of opportunities? and (2) Which is the north that must guide the future Chilean educational policy and, in that context, which are the high-priority challenges that are necessary to face?  This article contributes answers to both questions. In his first part reviews the main transformations that have introduced to the Chilean educative system in the last 25 years. In his second part, the article responds to the question on like advancing towards an education of quality for all.  Having like north the fundamental keys of the effectiveness and the educative improvement of the schools in Chile, the third part and end of the article, reflects on the policy alternatives that are necessary to consider to advance towards that north.